Invasive pulmonary aspergillosis due to Aspergillus lentulus in an adult patient: A case report and literature review. Issue 7 (July 2019) - Yagi, Kazuma; Ushikubo, Mari; Maeshima, Arafumi; Konishi, Misako; Fujimoto, Kazuyuki; Tsukamoto, Masako; Araki, Kazuhiro; Kamei, Katsuhiko; Oyamada, Yoshitaka; Oshima, Hisaji
Abstract: Aspergillus fumigatus is the commonest cause of pulmonary aspergillosis; however, a recently developed molecular genetic technique identified A. lentulus as a sibling species. Most of the isolates were found in solid organ recipients, often associated with a fatal outcome. Moreover, there is concern that A. lentulus has low susceptibility to multiple antifungal agents. Herein, we report an adult immunocompromised patient with proven invasive pulmonary aspergillosis (IPA) caused by A. lentulus, which was identified through molecular genetic analysis. The patient was diagnosed with IPA by bronchoscopy 3 weeks after initiating systemic corticosteroid therapy for anti-neutrophil cytoplasmic antibody-associated vasculitis. The clinical course of IPA due to A. lentulus showed improvement after treatment with the antifungal agent voriconazole. In summary, we report an adult immunocompromised patient without a history of transplantation who was diagnosed with IPA due to A. lentulus successfully treated with voriconazole, and we also report the findings of a literature review on IPA caused by A. lentulus .